A Study On The Influence Of Covid’19 On Individuals’ Perception Towards Impact Investment - et. al., Ms. O. Lakshmi Pratyusha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Investments undertaken with an intention of generating measurable socio-environmental benefits to solve the global issues like poverty, unemployment, climate change along with giving financial benefit to the investors is the point of discussion in this study. Impact Investments try to fill the gap to achieve United Nations Sustainable Development Goals (SDGs) which solve the global issues and try to create sustainable development. This study has been undertaken during the global pandemic which brings in a significant influence and a shift on the individual investors’ perception on social impact. The paper is approached in an empirical study, designed with primary data collected using sampling technique. With the findings on individuals’ perception on social investments, it could provide the right perception towards social investments and can lend in making a healthy environment possible with the private capital solving the global issues.